Estimativas de perdas de grãos de milho à granel no transporte rodoviário - Pereira, Pedro Silvério Xavier (2021)
Losses in grain transport occur due to road conditions, the condition of the trucks, overload, type of product transported and speed of transport. The objective was to establish a loss index in relation to the volume transported, per kilometer traveled (kg/km), per ton transported (kg/t) as well as to value these quantitative losses (R$/t) during the road transportation in bulk of corn. The assessments were carried out on the BR-163 highway, between the cities of Lucas do Rio Verde and Rondonópolis in the state of Mato Grosso, the main and most important grain transportation hub in the country. The study was based on the data of packing lists obtained from transport companies and warehouses accredited by CONAB. These packing lists provided the weight at the origin, and the weight at the destination, place of origin and destination, so, by difference, the amount of grain lost in transport and the mileage traveled in each route was obtained. It was evaluated, through sensors, the variation of humidity and air temperature around the mass of grains during road transport as well as the vibrations suffered by the body. Total losses were 1.808.951 kg, averaging 45,63 kg of loss per trip. The loss per km was on average 0,072 kg. The percentage loss rate for the corn crop was determined (0,1025%). Grain collection points were established along the highway. It was verified that the points of lower losses of corn grains were collected where the highway was in good traffic conditions. Interviews were carried out with approximately 500 truck drivers transporting loads of corn kernels. The predominant bodies in the transportation of grain in bulk are of the bulk type. The data indicate that 87% of the trucks and 84% of the bodies are in good or excellent condition. The most lost grain in transport, according to drivers, is corn and soybeans, which together account for approximately 40% of losses. Using an instrument equipped with humidity, temperature, gyroscope, accelerometer, and GPS sensors capable of performing readings and storing the collected data. This instrument was installed in the grain mass inside the truck bodies in the city of Lucas do Rio Verde and was removed in the city of Cuiabá, in six trucks, in addition to a sample of grains taken at both moments of installation and removal of the instrument. With the analyzes carried out, in the grain moisture determined in the greenhouse, there was an average decrease of 0,31% in the water content of the sample taken in the city of Cuiabá in relation to the Lucas do Rio Verde sample. significant, maintaining constant values in the six trips made, in the variable disturbances suffered by the bodywork there was a greater concentration of impacts in a certain range of values, showing that there is a pattern of irregularities in a certain stretch of the highway that cause these impacts. It is concluded that grain losses in the transport of bulk corn are occurring mainly due to poor maintenance of the highways. Holes and chatter are the main causes. The technology applied to the lining of the truck proved to be effective in reducing losses in road transport.